The results descemet-stripping automated endothelial keratoplasty at bullous keratopathy - S. V. Trufanov (Oftalʹmologiâ, 2014)
Purpose: to evaluate outcomes of the descemet-stripping automated endothelial keratoplasty using eye drops Kombinil-Duo dur- ing postoperative period.Methods: 26 patients suffered from bullous keratopathy underwent descemet-stripping automated endothelial keratoplasty using our own technique. We applied eye drops Kombinil-Duo during postoperative period.Results: 25 patients had clear corneas whole period of observation. Graft rejection occurred in 1 eye. Mean BSCVA was 0.47±0.21.Conclusion: Kombinil-Duo has been allowed to avoid infectious complication and to increase efficiency of the operative interven-tion during postoperative period.